KEARIFAN LOKAL MASYARAKAT PESISIR CIREBON DALAM MENJAGA EKOSISTEM: Praktik Kearifan Lokal Masyarakat Pesisir Cirebon dalam Menjaga MangroveB.Nilai-Nilai Sosial, Budaya, dan Agama yang Mendasari Masyarakat dalam Merawat Ekosistem MangroveC.Faktor-Faktor yang Mempermudah dan Menjadi Kendala bagi Masyarakat dalam Menerapkan Kearifan Lokal untuk Melestarikan MangroveAbstract: This study explores the local wisdom of coastal communities in Cirebon in preserving mangrove ecosystems and the social, cult - Tri Oktavia Ramadhani; Faiza Nur Rachman; Ratna Puspitasari (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2026)
This study explores the local wisdom of coastal communities in Cirebon in preserving mangrove ecosystems and the social, cultural, and religious values that support it. Using a descriptive qualitative approach through literature review, the study finds that conservation efforts include collective planting, customary norms, ecological traditions, limited use, and community-based monitoring. While these practices strengthen environmental sustainability and social solidarity, economic pressures and limited awareness remain challenges. Collaboration among stakeholders is therefore essential to sustain mangrove preservation.